PEDAGOGICAL MECHANISMS FOR FORMING THE HARMONY OF NATIONAL AND UNIVERSAL VALUES IN STUDENTS - Jurayev , Bobomurod; Xojiyeva , Matluba (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article provides a theoretical and methodological analysis of the pedagogical mechanisms for forming the integration of national and universal values among students in higher education. The study, based on an axiological approach, reveals the content of value integration and systematizes such mechanisms as content-integrative, motivational-axiological, activity-oriented, reflexive-analytical, and socio-cultural mechanisms. In addition, the pedagogical conditions ensuring the effectiveness of these mechanisms are substantiated. The results of the study contribute to ensuring the moral and ethical development of students within the higher education system.